Learning Biology Through the Ethnoscience-PBL Model: Efforts to Improve Students' Scientific Thinking Skills - Lia Sania Nur Haulia; Sri Hartati; Asrianty Mas'ud (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
This study was intended to analyze the effect of the ethnoscience-based Problem Based Learning (PBL) model on scientific thinking skills in reproductive system material. This research is a quasi-experimental design in the form of a pretest-posttest non-equivalent control group design. This research was conducted at class XI MIPA students for the 2022/2023 academic year in Sumedang. The research instruments used were pretest-posttest sheets and questionnaires. The data collection technique used in this study included a test of 15 essay questions and a questionnaire. The data analysis technique used is the normality test, independent sample t-test, and N-Gain test. The results showed that the students' scientific skills increased significantly after applying the ethnoscience-based learning model on the material of reproductive system. The independent sample t-test obtained p-value = 0.000 <0.05, which was significantly different between the posttest and pretest scores. N-Gain also obtained an average of 0.75 which indicates an increase in students' scientific skills in high category. The results of students' responses to learning with the ethnoscience-based PBL model on students' scientific thinking skills were included in very good category with an overall percentage of 82.5%. This study concluded that students' scientific thinking experienced an increase after learning through the ethnoscience-based PBL model on the reproductive system material.